2009
DOI: 10.1111/j.1469-0691.2009.03011.x
|View full text |Cite
|
Sign up to set email alerts
|

Free-living amoebae, a training field for macrophage resistance of mycobacteria

Abstract: Mycobacterium species evolved from an environmental recent common ancestor by reductive evolution and lateral gene transfer. Strategies selected through evolution and developed by mycobacteria resulted in resistance to predation by environmental unicellular protists, including free-living amoebae. Indeed, mycobacteria are isolated from the same soil and water environments as are amoebae, and experimental models using Acanthamoeba spp. and Dictyostelium discoideum were exploited to analyse the mechanisms for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 116 publications
(180 reference statements)
4
90
0
1
Order By: Relevance
“…Moreover, all of the colonies were conclusively identified using MALDI-TOF-MS as being the same Mycobacterium species as that used for the inoculation (El Khéchine et al, 2011). In particular, non-tuberculosis mycobacteria that are known as common soil inhabitants (Salah et al, 2009) were not identified in either control or inoculated plates. These observations are entirely novel for M. canettii.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, all of the colonies were conclusively identified using MALDI-TOF-MS as being the same Mycobacterium species as that used for the inoculation (El Khéchine et al, 2011). In particular, non-tuberculosis mycobacteria that are known as common soil inhabitants (Salah et al, 2009) were not identified in either control or inoculated plates. These observations are entirely novel for M. canettii.…”
Section: Discussionmentioning
confidence: 99%
“…Amoebae feed on mixed communities of bacteria within biofilms including, pathogenic bacteria such as species of Legionella, Mycobacterium, P. aeruginosa, Vibrio cholerae, Helicobacter pylori [6,12,45,46,59]. Once inside the amoebal cell, some bacteria will survive or escape the adverse conditions presented by digestive vacuoles, but can also find sanctuary from unfavourable environmental conditions and can multiply [25].…”
mentioning
confidence: 99%
“…Amoeba models allowed to investigate bactericidal mechanisms, phagocytosis and surface receptors. All tested Mycobacterium species were phagocytosed and were able to penetrate into amoebal vacuoles, including some species like M. tuberculosis that could survive in cysts under aerobic conditions (Salah et al, 2009). Endoparasites of FLA Legionella enter macrophages or amoeba by coiling phagocytosis after which it enters the phagosome.…”
Section: Interaction Between Fla and Bacteriamentioning
confidence: 99%
“…One of the interaction mechanisms by which M. avium spreads in the environment is the killing of infected amoeba (Koval, 1993;Cirillo et al, 1997;Matz and Jürgens, 2003). Salah et al (2009) provided a list of Mycobacterium species that were isolated from amoebal co-cultures. Amoeba models allowed to investigate bactericidal mechanisms, phagocytosis and surface receptors.…”
Section: Interaction Between Fla and Bacteriamentioning
confidence: 99%